SECULARISM IN INDIA MYTH OR REALITY: AN EXPLANATORY STUDY - Aqib Yousuf Rather (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2022)
An impetus was given to the discussion on whether or not Indian secularism is a myth or a reality. A secular society is one in which individuals are free to practise their religion of choice. The Constitution of India recognises and upholds the principle of religious toleration, making India a nation that is home to a number of distinct faiths. The term "secular" was not included in the original version of the Indian Constitution; nevertheless, it was added in 1976 as part of the 42nd Amendment. Nevertheless, the values of secular character have always been a part of the constitutional fabric of India, and this has been the case since the very beginning. The Judiciary has, on numerous occasions, drawn attention to this particular facet as well. It is possible to state with absolute certainty that secularism is one of the guiding principles of the Constitution and that this position will never be subject to revision. Nonetheless, there have been cases where the state has been seen to favour a specific religion over the concept of secularism. In order to better understand Indian secularism, we've written this piece. Secularism in India is described as a myth or reality and the issues related with it are discussed.